The Efficacy Of Herbal Plants Extract Against Infection Of Aeromonas Hydrophila, Staphylococcus Xylosus And Streptococcus Agalactiae In Snakehead (Channa Striata) Fish - Ali, Azirah Akbar (2014)
Preliminary screening was done for 13 plants species belonging to member of nine families such as Senna spectabilis, Jacaranda filicifolia, Samanae saman, Tamarindus indica, Carica papaya, Andira inermis, Morinda elliptica, Coleus aromaticus benth, Citrus hystrix, Milletia pinnata, Cymbopogon nardus, Cymbopogon citratus and Polyalthia longifolia were screened to find an antibacterial activity against three common fish pathogens namely Aeromonas hydrophila, Staphylococcus xylosus and Streptococcus agalactiae. Minimum Inhibitory Concentration (MIC) showed, S. xylosus was inhibited by S. saman with lowest concentration at 0.625 mg/ml compared to T. indica and J. filicifolia; 2.5 mg/ml respectively. Tamarindus indica and J. filicifolia showed activity against all pathogens tested. Toxicity test of brine shrimp was conducted on three selected plants extract by using Artemia salina nauplii as a test sample and from the results, T. indica and J. filicifolia were highly toxic; and S. saman shows lower toxicity (>1.0 mg/ml); with LC50 value of 2.22 mg/ml. Scanning electron microscope (SEM) were used to observe on two pathogens; S. xylosus and S. agalactiae treated with S. saman leaf extracts and showed structural damage in the treated cells. In addition, phytochemical analysis was conducted to investigate the chemical constitution in S. saman leaf extract; and found presence of alkaloid, flavonoid, tannins and polyphenolic compounds.